THE ROLE OF FAMILY FACTORS IN THE DEVELOPMENT OF ADAPTIVE ABILITIES OF THE GRADUATE SCHOOL - Вагапова, Альфия Равилевна (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2014)
Discusses the problem of development of adaptive abilities of graduates of schools. This paper discusses theoretical approaches to understanding the role of parental family in adaptation process. It is shown that the integral indicators of social and psychological adaptation depends on understanding of parental attitudes high school students , and the acceptability of the parental model determined by the level of conflict in the family. The use of complex techniques allowed us to study possible options for child-parent interaction (n = 40). In the case of identical types of parental behavior at display positive interest increase the values and adaptation possibilities. Ways of understanding of parental attitudes as a guideline, inconsistent, contradictory lead to reduction in integrative indicators of social and psychological adaptation. Also identified by sex - differences, it is shown that the most important for high school students has a positive perception of the father's position, as in the case of deviations difficult adaptation process, there is a trend toward a closed position to face interpersonal interaction. In the event of heightened conflict in parent-child relationship is noted difficult and unacceptable understanding of the parental role . The author comes to the conclusion that family factors play a significant role in the development of adaptive abilities. Applied aspect of research problem can be implemented in practice of psychological counseling services, and to develop programs to optimize the adaptation process.DOI:  http://dx.doi.org/10.12731/2218-7405-2013-12-7